Comparative Forms of Adjectives by Suffix –an in Toba Batak - Ambarita, Esron (The Explora, 2021)
The objectives of this study is to investigate word formations of comparative forms of adjectives by suffix [-an] in Toba Batak. Comparative forms of adjectives by suffix [-an] in Toba Batak are constructed without considering the number of syllables of the base forms of adjectives as those in English. Besides, the attachments of suffix [-an] to adjectives in Toba Batak to construct comparative forms do not require any phonological rules as those when attaching prefix [um-] to construct comparative form in Toba Batak. The stress of the words modified with suffix [-an] is in suffix [-an] itself. The meaning of suffix [-an] denotes comparative forms. It signifies more meaning than what is indicated in the base forms of the adjectives to which suffix [-an] is attached. In short, word formation of comparative form by suffix [-an] in Toba Batak can be done to all adjective bases in very simple way inflectionally.